COMPARISON OF DEFERASIROX AND DESFERRIOXAMINE AS IRON CHELATORS IN MULTI-TRANSFUSED PATIENTS OF Β-THALASSEMIA MAJOR - AHMED , A; KAMRAN, M; MUKHTAR, M; ALI , M; UMAIR, M (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to compare the efficacy of deferasirox and deferoxamine in improving hematological and immunological parameters in patients with transfusion-dependent β-thalassemia major. 200 patients were enrolled in the study, with 100 receiving deferasirox and 100 receiving deferoxamine. The study was conducted at Mayo Hospital, Lahore. The patients were followed up for six months, during which various hematological and immunological parameters were measured at regular intervals. The data were analyzed using appropriate statistical methods. Both deferasirox and deferoxamine effectively improved hematological and immunological parameters in patients with β-thalassemia major. However, deferasirox was more effective than deferoxamine in improving hemoglobin, red blood cell count, and hematocrit levels. In contrast, there was no significant difference between the two iron chelators in their impact on white blood cell count and platelet count. Deferasirox appears to be a more effective iron chelator than deferoxamine in improving hematological parameters in patients with transfusion-dependent β-thalassemia major